PEMBENTUKAN KARAKTER RELIGIUS DI TAMAN KANAK-KANAK MELALUI PEMBIASAAN KEGIATAN KEAGAMAAN - Erra Yuni Rindiani Erra; Arri Handayani; Dini Rahmawati (STKIP Subang, 2024)
This literature review journal presents a summary and synthesis of literature related to the formation of religious character in Early Childhood Education (ECE) through the habituation of religious activities. In exploring this topic, the literature review aims to identify patterns, trends, and findings emerging from previous studies, as well as to detail key aspects influencing the effectiveness of habituating religious activities in ECE. The literature review was conducted by scrutinizing academic databases, scholarly journals, and other reliable literature sources. The results of this literature review highlight several key themes related to the formation of religious character in ECE. Firstly, the literature confirms that habituating religious activities in ECE has a positive impact on the development of children's religious character. Activities such as daily prayers, learning religious stories, and participating in religious ceremonies help children comprehend moral and spiritual values more deeply. Secondly, the role of teachers and parents in supporting the formation of children's religious character in ECE takes center stage in the literature. Their active involvement in providing guidance, emotional support, and creating a supportive environment is crucial in achieving optimal outcomes. Furthermore, the literature also sheds light on challenges and obstacles that may be encountered in implementing habituation of religious activities in ECE. Some studies note differences in beliefs among parents, teachers, and ECE staff, as well as logistical constraints and a lack of resources as factors that can impact the effectiveness of the program. Overall, this literature review provides a comprehensive understanding of the concept of forming religious character through the habituation of religious activities in ECE. The implications of these literature findings can guide education practitioners, policymakers, and researchers to enhance the design and implementation of religious programs in ECE. With the existence of this literature review journal, it is expected that its contribution will complement academic understanding and provide guidance for further research in the context of forming the religious character of young children through the habituation of religious activities in ECE environments.